The Effect of the U.S. Quantitative Easing on the Term Structure. A Spatial Panel Model Approach - Almeida, Alejandro; Golpe, Antonio A.; Martín-Álvarez, Juan Manuel; Vides, José Carlos (Finance a Uver - Czech Journal of Economics and Finance, 2023)
In this paper, we apply the spatial panel model that accounts for serial dynamics, crosssectional dependence, and common factors to assess interest rate sensitivity across the term structure to changes in the policy rate. Considering the Quantitative Easing (QE) program as a breakpoint, we apply this method before and after implementing this program. First, results suggest the existence of spillovers between different maturities. Second, after QE implementation, the impact of monetary policy is influencing more time the interest rates, that is, it will be more persistent, and the influence of Federal Funds rate on Treasury Constant rates has changed, although remaining the same pattern where short-term maturities are more sensitive than long-term ones. Finally, our findings may suggest that the Fed would possess more controllability of the term structure and a more efficient transmission mechanism. These results possess important considerations to policymakers and the effectiveness of the monetary policy applied by the Fed.
Keywords: monetary policy; spatial panel model; yield curve; Scopus; JCR